Teaching sign language in gaucho schools for deaf people: a study of curricula - Carolina Hessel Silveira (Universidade Federal de Santa Maria (UFSM), 2013)
The paper, which provides partial results of a master's dissertation, has sought to give contribute Sign Language curriculum in the deaf schooling. We began to understand the importance of sign languages for deaf people's development and found out that a large part of the deaf are from hearing parents, which emphasises the significance of teaching LIBRAS (Brazilian Sign Language) in schools for the deaf. We should also consider the importance of this study in building deaf identities and strengthening the deaf culture. We have obtained the theoretical basis in the so-called Deaf Studies and some experts in the curriculum theories. The main objective for this study has been to conduct an analysis of the LIBRAS curriculum at work in schools for the deaf in Rio Grande do Sul, Brazil. The curriculum analysis has shown a degree of diversity: in some curricula, content from one year is repeated in the next one with no articulation. In others, one can find preoccupation for issues of deaf identity and culture, but some of them include contents that are not related to LIBRAS, or the deaf culture, but rather to discipline for the deaf in general. By providing positive and negative aspects, the analysis data may help in discussions about difficulties, progress and problems in LIBRAS teacher education for deaf students.